2010
DOI: 10.1179/joc.2010.22.1.58
|View full text |Cite
|
Sign up to set email alerts
|

Oral Ibandronate in Metastatic Bone Breast Cancer: The Florence University Experience and a Review of the Literature

Abstract: Ibandronate is an amino-bisphosphonate approved in metastatic breast cancer to reduce skeletal complications and to alleviate bone pain. we report our experience about the safety of oral ibandronate and review the literature.We treated 44 patients and administered 524 cycles of oral ibandronate (a single cycle was defined as a 50 mg capsule once daily for 28 days) with a median of 12 cycles (range 6-24). At a median follow-up of 18.5 months (range 6-28) the mean pain score decreased from 1.59 (SD+/-0.97) at ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 39 publications
(50 reference statements)
1
4
0
Order By: Relevance
“…During postmarketingsurveillanceforupto24weeksofthe712patients reporting pain at baseline, 70% showed improvement after ibandronatetreatment(i.v.andoral)withameanoveralldecreaseinpainscoreof1.6(p<0.0001) [63].Meanpainscores were reduced in 205 patients previously treated with other bis phosphonates (-1.0; p < 0.0001) and in 59 patients with prioribandronatetreatment(-0.5;p=0.0108).Therewasno overall change in performance status in this study. A case series of 44 patients showed similar findings [64]. After a median of 12 28-day cycles of oral ibandronate 50 mg daily, themeanpainscore(5-pointvisualanaloguescale,VAS)decreased from 1.59 to 0.41 (median follow-up 18.5 months).…”
Section: Administration and Tolerability Of Ibandronatesupporting
confidence: 59%
“…During postmarketingsurveillanceforupto24weeksofthe712patients reporting pain at baseline, 70% showed improvement after ibandronatetreatment(i.v.andoral)withameanoveralldecreaseinpainscoreof1.6(p<0.0001) [63].Meanpainscores were reduced in 205 patients previously treated with other bis phosphonates (-1.0; p < 0.0001) and in 59 patients with prioribandronatetreatment(-0.5;p=0.0108).Therewasno overall change in performance status in this study. A case series of 44 patients showed similar findings [64]. After a median of 12 28-day cycles of oral ibandronate 50 mg daily, themeanpainscore(5-pointvisualanaloguescale,VAS)decreased from 1.59 to 0.41 (median follow-up 18.5 months).…”
Section: Administration and Tolerability Of Ibandronatesupporting
confidence: 59%
“…It has also been determined to have similar safety in terms of side-effects [11]. One study of oral ibandronate in 44 patients determined a mean follow-up duration of 18.5 months, with no impairment in renal function [12]. Renal toxicity associated with ibandronic acid was so low as to be equivalent to placebos [4].…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, the nephrotoxicity of ibandronic acid is extremely low and equivalent to that of the placebo. Another study [ 17 ] conducted on 44 patients treated with ibandronate (IBA) reported no impairment of renal function during an average follow-up of 18.5 months. In addition, Han et al [ 18 ] noted that the pain relief rate and improvement in the quality of life in patients with bone tumors were higher in the ibandronic acid group than in the zoledronic acid group ( P < 0.05).…”
Section: Introductionmentioning
confidence: 99%